Corporate entrepreneurship on Government Linked Companies performance: the role of perceived environmental munificence and dynamism as moderating variables / Ibrahim Awang Besar - Awang Besar, Ibrahim (Institute of Graduate Studies, UiTM, 2017)
Financial performance of the Government Linked Companies (GLCs) has been the subject of public scrutiny and their performance has always been compared with the performance of non-government linked companies (non- GLCs). Generally, GLCs performance is said to be underperformed as compared to non-GLCs and continues to be a major concern. A tall order was given to GLCs to improve their financial performance by advocating innovation, proactiveness and risk-taking as means of transforming the economy from a knowledge-based to innovation-based economy. The aim of this research is to examine the effects of corporate entrepreneurship dimensions on organization’s financial performance of GLCs in Malaysia. In addition, external factors such as munificence and dynamism were injected to examine if these variables do moderate the relationship between the corporate entrepreneurship and financial performance. Scales for dimensions of corporate entrepreneurship, financial performance and environmental munificence and dynamism have been adopted from the existing literature. Using usable data of 282 from the 450 respondents as a sample frame, across diverse industries such as construction, consumer products, finance, industrial products, infrastructure, plantation, properties and trading and services, this research analyzes the effect of corporate entrepreneurship dimensions on financial performance of GLCs…